Radical metastasectomy followed by sorafenib versus observation in patients withclear cell renal cell carcinoma: extended follow -up of efficacy results from the randomized phase II RESORT trial. Issue 2 (1st February 2021) - Mennitto, A.; Verzoni, E.; Cognetti, F.; Miceli, R.; Milella, M.; Mosca, A.; Chiuri, V. E.; Bearz, A.; Morelli, F.; Ortega, C.; Atzori, F.; Donini, M.; et al.
ABSTRACT: Background : The RESORT trial showed no longer relapse free survival (RFS) with sorafenib following radical metastasectomy in metastatic renal cell carcinoma. We present the updated 42-month follow-up data. Methods : The phase II RESORT trial randomized patients to sorafenib or observation within 12 weeks from surgery. RFS was the primary endpoint. Results : We analyzed 68 patients (32 in sorafenib and 36 in the observation arm), randomized between November 2012 and November 2017. Eighty-one percent in the sorafenib arm and 80% in the observation arm had one metastasis . At a median follow-up of 42 months (interquartile range 31–58), in the observation arm the median RFS was 35 months, RFS probability was 57% (95% CI 42–76%) at 24 and 44% (95% CI 30–65%) at 48 months. In the sorafenib arm, median RFS was 21 months, RFS probability was 50% (95% CI 34–71%) at 24 and 32% (95% CI 18–57%) at 48 months (p = 0.342;HR 1.35;95% CI 0.72–2.54). Forty-seven percent and 37.5% of the patients in the two arms, respectively, are disease free. The site of relapses was independent of the previous metastasectomy site. Expert commentary: Sorafenib after metastasectomy did not improve RFS, but surgery in selected patients should be considered in order to potentially improve survival. Clinical trial registration : www.clinicaltrials.gov identifier is NCT0144480